#TITLE_ALTERNATIVE# - SANDI ARYADI (NIM 13103095), BAYU
Articulated bus has been produced and operated by many developed countries as mass rapid transit since long time. Today, Indonesia is also interested to operate it as transportation problem solution. Since bus manufacturer still learn to integrate and produce it, the understanding about articulated bus's technology is not sufficient. Purposes of this analysis based of reasons above are to predict dynamical behavior and to formulate design parameters and their effects to articulated bus dynamic behavior. The scope of analysis is pusher type articulated bus which include three-axles layout and four-axles layout. This final project started with literatures study and articulated bus lay outs arrangement. Vehicle dynamic analysis is limited only for these lay outs. This vehicle dynamic analysis include Ackerman geometry arrangement, simple handling model arrangement, mathematical model formulation, and transfer function formulation. Simulations are using step steer input. There are two conclusion from this vehicle dynamic analysis. Pusher type articulated bus is stable system if traction force is small or if torsional damper is added to turntable. Respond time of three axles articulated bus is faster than four axles articulated bus.